Microalgae Chlorella vulgaris and Scenedesmus dimorphus co-cultivation with landfill leachate for pollutant removal and lipid production. (December 2021) - Hu, Dan; Zhang, Jiaxing; Chu, Ruoyu; Yin, Zhihong; Hu, Jiangjun; Kristianto Nugroho, Yohanes; Li, Zhaohua; Zhu, Liandong
Graphical abstract: Highlights: Landfill leachate was pretreated with NaClO. First time to treat leachate by the co-cultivation of C. vulgaris and S. dimorphus. The suitable dilution ratio for the growth of C. vulgaris and S. dimorphus was 10%. Co-culture of C. vulgaris and S. dimorphus could improve the activity of algal cells. C16 to C18 in co-culturing group accounted for 88.81%. Abstract: In this study, landfill leachate was pre-treated with NaClO, and then diluted to 5%, 10% and 15% for microalgae growth of Chlorella vulgaris and Scenedesmus dimorphus in the mono- and co-culture modes to investigate the nutrient removal and growth characteristics of microalgae. The results revealed that landfill leachate with the 10% dilution rate was conducive for microalgae growth and exhibited robust biomass growth and the highest nutrient removal efficiency. The co-culture biomass in 10% landfill leachate achieved 0.266 g/L within 10 days and demonstrated the improved nutrient utilisation efficiency of microalgae. In addition, the chemical oxygen demand, ammonia nitrogen, total nitrate and total phosphorus removal efficiencies accordingly reached 81.0%, 80.1%, 72.1% and 86.0% in 10% landfill leachate. Meanwhile, both the enzyme activity and fluorescence parameters proved that the cell activity of co-culture was higher than that of mono-culture.